(untitled) (UNIZIK Journal of Educational Management and Policy, 2024)
This research investigated the effects of information and communication technology during coronavirus pandemic in secondary school in Awka south local government area of Anambra state. The population of the study comprised of 495 teachers in the 19 public secondary schools in Awka South L.G.A. of Anambra State. Multi-stage sampling technique was used to select 10 public secondary schools, out of the 19 public secondary schools in Awka south, while 25 teachers were randomly selected from each of the 10 schools to give rise to the sample of 250 teachers. The researcher designed a questionnaire related to the subject matter. Data collected in the study were analyzed using mean; the raw scores were presented in tables showing relative frequencies of each item or group of items. Findings of the study are grouped into, positive and negative aspect. On the positive aspect, students were able to learn online during the Coronavirus Lockdown, students were able to get ICT knowledge and skills in their various schools prior to the Coronavirus Pandemic Lockdown, students were able to carry out some research on their own concerning the non-familiar terms used by their teachers in the course of teaching, students were able to provide answers to the assignment given to them and explore more online. While on the negative aspect, the results showed that students usually missed online classes since data was expensive, they encountered the issue of poor power supply while learning online, network always affect classes in session, because they do not have enough computer facilities, learning wasn’t that easy, some teachers do not know how to teach using online mechanism, some teachers preferred classroom teaching to online teaching